PENGARUH KUALITAS LAYANAN, KEPERCAYAAN DAN KOMITMEN TERHADAP LOYALITAS PELANGGAN (Studi pada Bengkel Yamaha SS Motor Semarang) (Students' Journal of Economic and Management, 2014)
This study aims to analyze the effect of service quality, trust and commitment to customer loyalty Repair Motorcycles Yamaha SS Semarang. The population in this study were all people who use the services of repair / sevice in Yamaha SS Motor Repair Semarang. Because the population is not known with certainty, then the sampling based on the formula proposed by Taro in order to obtain a sample of 100 people. Test equipment used in this study testing the validity using factor analysis, reliability testing using Cronbach Alpha and hypothesis testing using multiple linear regression. The results of the analysis can be concluded that: (1) the positive effect of service quality on customer loyalty. (2) the trust has positive effect on customer loyalty. (3). commitment to a positive effect on customer loyalty. Keywords: service quality, trust, commitment and customer loyalty